In Silico Study of Cucurbita maxima Compounds as Potential Therapeutics Against Schistosomiasis - Mtemeli, Floryn Lynorah; Shoko, Ryman; Ndlovu, Joice; Mugumbate, Grace (SAGE Publications, 2022)
Schistosomiasis, a disease usually related to poverty and poor sanitation, affects more than 200 million people worldwide. Since the 1970s, the medical sector has depended on a single drug, praziquantel, for the treatment of the disease. The emerging evidence of resistance of the Schistosoma parasite to praziquantel and the drug’s inefficacy against juvenile stages of the parasite makes the need to find alternative drugs an urgent matter. In this study, we explored the inhibition potential of compounds from Cucurbita maxima using molecular docking studies on Schistosoma mansoni purine nucleoside phosphorylase (SmPNP) and Schistosoma haematobium 28-kDa glutathione S-transferase (Sh28kDaGST). Following molecular docking studies and analysis of the active sites, the primary amino acids that were observed and shown to be involved in the SmPNP-ligand interaction are CYS 33, ARG 86, HIS 88, TYR 90, ALA 118, ALA 119, PRO 200, TYR 202, GLU 203, VAL 219, MET 221, THR 244, ASN 245, PRO 257 and HIS 259. For the Sh28dKa-ligand interaction, the primary amino acids were PHE 11, ARG 16, TRP 41, LEU 53, GLU 70 and SER 71. Momordicoside I aglycone binds to SmPNP with the lowest binding affinity of -7.9 kcal/mol by pi sigma bond interactions with HIS 88. Balsaminoside B binds to Sh28kDaGST with a binding affinity of −7.6 kcal/mol by hydrogen bond interaction with TRP 41, LEU 53 and SER 71. Pharmacokinetic studies showed favourable drug-like properties for the 10 compounds that exhibited the lowest binding energies. Therefore, we propose that bioactive compounds from C. maxima be considered as potential novel drug hits in the treatment of schistosomiasis.